Bacterial chromatin: methods and protocols - Dame, Remus (Methods in molecular biology, 2018)
Determination of the 3D Genome Organization of Bacteria using Hi-C -- Overview of Processing and Analyzing Hi-C Data on Bacteria -- GeF-seq：A Simple Procedure for Base Pair Resolution ChIP-seq -- Genomic SELEX Screening of Regulatory Targets of Escherichia coli Transcription Factors -- Modular assembly of Synthetic Secondary Chromosomes -- High-resolution Characterization of DNA/Protein Complexes in Living Bacteria -- Imaging of Transcription and Replication in the Bacterial Chromosome with Multicolor Three-dimensional Superresolution Structured Illumination Microscopy -- Genetic Approaches to Study the Interplay Between Transcription and Nucleoid-associated Proteins in Escherichia coliAtomic Force Microscopy Imaging and Analysis of Prokaryotic Genome Organization -- Dynamic Light Scattering of DNA-ligand Complexes -- Microscale Thermophoresis Analysis of Chromatin Interactions -- Quantitative Determination of DNA Bridging Efficiency of Chromatin Proteins -- Approaches for Determining DNA Persistence Length using Atomic Force Microscopy -- Quantitation of DNA Binding Affinity using Tethered Particle Motion -- Observing Bacterial Chromatin Protein-DNA Interactions by Combining DNA Flow-stretching with Single-molecule Imaging -- Unravelling the Biophysical Properties of Chromatin Proteins and DNA using Acoustic Force Spectroscopy -- Unravelling DNA organization with single-molecule Force Spectroscopy using Magnetic Tweezers -- In Vitro Transcription Assay to Quantify Effects of H-NS Filaments on RNA Chain Elongation by RNA Polymerase -- Deciphering 3D Organization Of Chromosomes using Hi-C Data -- Molecular Dynamics Simulation of a Feather-boa Model of Bacterial Chromosome. .
Keywords: Chromatin; Bakterien